ANALISIS PENGARUH PENGADOPSIAN IFRS, KARAKTERISTIK PERUSAHAAN, DAN KEPEMILIKAN BLOCKHOLDER TERHADAP MANAJEMEN LABA - Agus Fahrul Chair (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
The aims of this research are to determine the effect of IFRS Adoption, Firm Size, Leverage and Blockholder Ownership to Earnings Management. The research conducted on manufacturing companies listed on the Indonesia Stock Exchange (BEI) period of 2012-2015. Sample of this research consist of 64 companies using purposive sampling method. Earnings Management is proxied with discretionary accruals and measured using a modified jones model. IFRS Adoption measured by Dummy Variables. Firm Size measured by logarithm base ten. Leverage measured by Debt to Total Asset Ratio (DTA) and Blockholder Ownership measured by Dummy Variables. The results in this study showed that there was a positive and insignificant influence between the adoption of IFRS on earnings management, firm size variable had a negative and insignificant effect on earnings management, leverage variable had a positive and significant effect on earnings management and blockholder ownership had a negative and insignificant effect on earnings management. This research is expected to provide input to users of financial statements as decision makers and to parties with an interest in financial reports regarding the importance of quality financial report information, especially information regarding earnings management